Creating Satisfaction and Loyalty with Service Encounter and Servicescape at Balung Hospital Jember Regency - Tri Palupi Robustin; Nanik Hariyana (Jurnal Manajemen Pelayanan Publik, 2024)
The quality of service provided by the hospital will affect satisfaction and can create customer loyalty. One form of service in a hospital is service encounter and servicescape. Services at Balung Hospital still receive negative ratings in the eyes of the public because the services provided are not in accordance with consumer expectations. The purpose of this study is to determine how the influence of service encounter and servicescape on satisfaction and loyalty both directly and indirectly. The sample size of this study was 105 respondents and data analysis techniques using SEM (Structural Equation Modeling). The results of the study indicate that first, service encounter can create satisfaction. Second, servicescape can create satisfaction. Third, service encounters can create loyalty. Fourth, servicescape cannot create loyalty directly, but indirectly with the mediating role of satisfaction can create loyalty. And fifth, satisfaction can create loyalty.